Identification of Conflict Resolution in Civil Relations between Boarding House Owners and Boarding House Residents (Study at Semarang State University Campus Circle) - Ansori, Rio Taufik; Puspitasari, Saniya; Azra, Vira; Putra, Tegar Islami; Niravita, Aprila (The Indonesian Journal of International Clinical Legal Education, 2023)
This study aims to investigate conflict resolution between residents and boarding house owners in civil relations near the Semarang State University campus. Utilizing a mixed-methods approach, combining normative juridical research with empirical field data, the research discovered that the majority of conflicts are resolved through non-litigious channels. The legal framework for out-of-court settlements aligns with Law No. 30 of 1999 on Alternative Dispute Resolution. Notably, the civil relationship dynamics around the UNNES campus involve a lease agreement between property owners and tenants, whether formalized in writing or conveyed orally. The study sheds light on the prevalence of non-litigation methods in resolving conflicts, emphasizing the significance of alternative dispute resolution mechanisms. This research contributes valuable insights into the legal aspects of the landlord-tenant relationship, providing a nuanced understanding of the complexities in civil relations within the context of university campus housing.